Impact of Hba1c Levels on Maternal and Neonatal Outcomes - Hana Alfurjani; Zeinab Saleh; Laila Almahdi; Huda Othman; Nasreen Osman; Namat Abid (AlQalam Journal of Medical and Applied Sciences, 2021)
Background and Objective. Diabetes mellitus is a metabolic disorder characterized by the presence of hyperglycemia due to defective insulin secretion, defective insulin action or both. This study aimed to assess the clinical utility of early and late trimester HbA1c level in predicting adverse pregnancy outcome in Gestational DM (GDM) and PGDM. Methods. This study was retrospective case series study conducted in Aljala hospital of Tripoli, Libya during the year 2014-2015. One hundred and thirty-five diabetic patients were randomly selected from the hospital files. The following data was obtained from the files: the age, gravidal history, type of DM, treatment of DM, HbA1c level in early and late pregnancy, gestational age, maternal outcomes (HTN, Preeclampsia, UTI, hypothyroid, diabetic complications) and neonatal outcomes (IUGR, NN sepsis, RDS, NN hypoglycemia, birth injury, congenital anomaly, apgar score, birth weight and NN polycythemia. Results. The mean age of the patients was 35.42 years. The majority of the patients were type 2 diabetes with mean HbA1c in early pregnancy of 7.8. In the late stage of pregnancy, the mean HbA1c was lower 7.2. The study revealed that there were no relations between early HbA1c and outcomes (maternal and neonatal) with p value > 0.05. The study also showed insignificant relation between the changes of HbA1c levels during the pregnancy and the outcome (maternal and neonatal) with p value > 0.05. Conclusion. Although HbA1c levels are important in pregnancy to monitor the compliance of the treatment, the use of HbA1c level to predict the adverse maternal and neonatal outcomes remains questionable.